2013
DOI: 10.1016/j.jaac.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Substance Use in the Multimodal Treatment Study of Attention-Deficit/Hyperactivity Disorder (ADHD) (MTA) as a Function of Childhood ADHD, Random Assignment to Childhood Treatments, and Subsequent Medication

Abstract: Objectives To determine long-term effects on substance use and substance use disorder (SUD), up to 8 years after childhood enrollment, of the randomly assigned 14-month treatments in the multisite Multimodal Treatment Study of Children with Attention-Deficit/Hyperactivity Disorder (MTA; n=436); to test whether (a) medication at follow-up, (b) cumulative psychostimulant treatment over time, or (c) both relate to substance use/SUD; to compare substance use/SUD in the ADHD sample to the non-ADHD childhood classma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
179
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 76 publications
10
179
1
10
Order By: Relevance
“…For example, when frequency measures of drinking are considered in adolescence (beyond just use/ nonuse as refl ected in the studies considered by Lee et al, 2011), group differences emerge by late adolescence (Molina et al, , 2007. Similarly, in a large multisite sample of children with ADHD, repeated drinking or drunkenness in adolescence was elevated for the ADHD compared with the non-ADHD group (Molina et al, 2013). Thus, beginning in adolescence, there is an emerging vulnerability to later problematic alcohol use that warrants further research.…”
Section: Attention-defi Cit/hyperactivity Disorder and Adolescent Alcmentioning
confidence: 99%
“…For example, when frequency measures of drinking are considered in adolescence (beyond just use/ nonuse as refl ected in the studies considered by Lee et al, 2011), group differences emerge by late adolescence (Molina et al, , 2007. Similarly, in a large multisite sample of children with ADHD, repeated drinking or drunkenness in adolescence was elevated for the ADHD compared with the non-ADHD group (Molina et al, 2013). Thus, beginning in adolescence, there is an emerging vulnerability to later problematic alcohol use that warrants further research.…”
Section: Attention-defi Cit/hyperactivity Disorder and Adolescent Alcmentioning
confidence: 99%
“…Children with ADHD are at risk of school failure, emotional difficulties, substance misuse, antisocial behaviour, and poor peer relationships in adolescence 8, 9, 10, 11, 12, 13, 14, and are more impaired in psychosocial, educational, and neuropsychological functioning as adults 15. ADHD affects both boys and girls in all areas of functioning, for example, academically, cognitively, psychosocially, and psychiatrically 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30.…”
Section: Introductionmentioning
confidence: 99%
“…ADHD affects both boys and girls in all areas of functioning, for example, academically, cognitively, psychosocially, and psychiatrically 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30. Even though ADHD is associated with coexisting externalizing and internalizing disorders in both genders, girls with ADHD are significantly more likely to display internalizing disorders than boys with ADHD 25, 31, 32, 33.…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 study, the Multimodal Treatment Study for ADHD (MTA Study), employed random assignment to medication conditions or included a placebo comparison. At 8-year follow-up, no significant association was reported between ever receiving stimulant treatment and ND diagnosis 12 ; however, additional data provided by the author indicated that for youth who continued to take stimulant medication more than 50% of the time at follow-up, medication was associated with lower rates of daily smoking (OR = 0.51 [95% CI: 0.27-0.97]).…”
Section: Figurementioning
confidence: 92%
“…5,6 Youth with ADHD are 2 to 3 times more likely to smoke cigarettes than their peers without ADHD. [7][8][9][10][11][12] They also begin smoking earlier 7,13 and progress more quickly to regular use and dependence. 8 ADHD youth smokers are also at higher risk for drug and alcohol use disorders than youth with ADHD who do not smoke.…”
mentioning
confidence: 99%